The functional diversity–productivity relationship of woody plants is climatically sensitive - Haoru Yan; Bernhard Schmid; Wubing Xu; Franca J. Bongers; Guoke Chen; Ting Tang; Zhiheng Wang; Jens‐Christian Svenning; Keping Ma; Xiaojuan Liu (Ecology and Evolution, 2024)
Abstract Plot‐scale experiments indicate that functional diversity (FD) plays a pivotal role in sustaining ecosystem functions such as net primary productivity (NPP). However, the relationships between functional diversity and NPP across larger scale under varying climatic conditions are sparsely studied, despite its significance for understanding forest–atmosphere interactions and informing policy development. Hence, we examine the relationships of community‐weighted mean (CWM) and functional dispersion (FDis) of woody plant traits on NPP across China and if such relationships are modulated by climatic conditions at the national scale. Using comprehensive datasets of distribution, functional traits, and productivity for 9120 Chinese woody plant species, we evaluated the distribution pattern of community‐weighted mean and functional dispersion (including three orthogonal trait indicators: plant size, leaf morphology, and flower duration) and its relationships with NPP. Finally, we tested the effects of climatic conditions on community‐weighted mean/functional dispersion–NPP relationships. We first found overall functional diversity–NPP relationships, but also that the magnitude of these relationships was sensitive to climate, with plant size community‐weighted mean promoting NPP in warm regions and plant size functional dispersion promoting NPP in wet regions. Second, warm and wet conditions indirectly increased NPP by its positive effects on community‐weighted mean or functional dispersion, particularly through mean plant size and leaf morphology. Our study provides comprehensive evidence for the relationships between functional diversity and NPP under varying climates at a large scale. Importantly, our results indicate a broadening significance of multidimensional plant functional traits for woody vegetation NPP in response to rising temperatures and wetter climates. Restoration, reforestation actions and natural capital accounting need to carefully consider not only community‐weighted mean and functional dispersion but also their interactions with climate, to predict how functional diversity may promote ecosystem functioning under future climatic conditions.